2021
DOI: 10.1108/jsocm-10-2020-0210
|View full text |Cite
|
Sign up to set email alerts
|

A review of social marketing interventions in low- and middle-income countries (2010–2019)

Abstract: Purpose This study aims to review social marketing interventions reported in peer-reviewed literature from 2010 to 2019 that were conducted in low- and middle-income countries (LMICs). This paper seeks to further contribute to understanding on the health of the social marketing field, synthesising studies to examine the extent of use of social marketing’s core principles. Design/methodology/approach A total of 17 interventions, discussed in 31 papers, were identified in the review. Social marketing intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
3
11
0
Order By: Relevance
“…This finding was partially reflected in practice, with segmentation (49%) and theory (19%) the most underused concepts (noting that theory maybe even more under-reported in practitioner databases than academic articles). Similarly to our umbrella review in Strand 2, Firestone and colleagues (2017) and Schmidtke et al (2021) identified theory, competition, segmentation and exchange as the four least applied principles across more than 100 interventions in low-and middle-income settings in countriesfurther confirming our findings of the limited application of the social marketing principle and/or documentation. Until today, work on behaviour change often lacked value propositions that exchange worthy (for example, Kubacki et al, 2015aKubacki et al, , 2015bKubacki et al, , 2015c, but it becomes increasingly evident that without it, some instantaneous exchange uptake is extremely unlikely (Firestone et al, 2017).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This finding was partially reflected in practice, with segmentation (49%) and theory (19%) the most underused concepts (noting that theory maybe even more under-reported in practitioner databases than academic articles). Similarly to our umbrella review in Strand 2, Firestone and colleagues (2017) and Schmidtke et al (2021) identified theory, competition, segmentation and exchange as the four least applied principles across more than 100 interventions in low-and middle-income settings in countriesfurther confirming our findings of the limited application of the social marketing principle and/or documentation. Until today, work on behaviour change often lacked value propositions that exchange worthy (for example, Kubacki et al, 2015aKubacki et al, , 2015bKubacki et al, , 2015c, but it becomes increasingly evident that without it, some instantaneous exchange uptake is extremely unlikely (Firestone et al, 2017).…”
Section: Resultssupporting
confidence: 83%
“…This paper demonstrates across Strands 2 and 3 that marketing is effective in changing behaviour to produce social benefits and thus expands our understanding of marketing’s important contribution towards behaviour change in the social, health and environmental domains. Social marketers have systematically looked back and assessed how interventions and programs have applied the principles of marketing (Kubacki et al , 2015a, 2015b, 2015c; Schmidtke et al , 2021; Stead et al , 2007) and demonstrated the concomitant growth in effectiveness with the application of more principles (Carins and Rundle-Thiele, 2014; Firestone et al , 2017; Xia et al , 2016). Our umbrella review extends this finding beyond nutrition (Carins and Rundle-Thiele, 2014), physical activity (Xia et al , 2016) and health (Firestone et al , 2017) by examining a broader range of domains such as environmental issues and social issues in addition to health, and as such continues to build, broaden and strengthen the evidence base.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…"Decolonise" Global North-oriented funding models and practices that perpetuate an imbalance of power and resources between Global North and South countries; address structural factors that promote inequity; and involve in-country scientists and researchers in decisions around funding that affects their region (Erondu et al, 2021) Actively discourage "parachute science", the practice where researchers from Global North countries conduct research within Global South countries while failing to sufficiently engage and involve individuals and organisations from those countries, and then complete the research process in their home countries without communicating with representatives of the countries where the research was carried out (Stefanoudis et al, 2021) If conducting research or social marketing interventions in a country with a different language, take steps to learn the local language before engaging with stakeholders and partners or visiting the location Encourage the use of ethnography in formative research to gain a deep understanding of behaviour (Brennan et al, 2015;Kariippanon et al, 2020) and continue to develop and adopt novel research methods (e.g., customer journey mapping, Cateriano-Arévalo et al, 2021) Widen the repertory of social marketing approaches, techniques and tools in the Global North by incorporating those from the Global South Continue testing theory and practice of "traditional" social marketing approaches that have been proven to be effective in some Global South contexts, such as the 4Ps (Schmidtke et al, 2021), macro-marketing (Bastos et al, 2021), socio-cultural approaches (Martam, 2016) and others, while explicitly identifying where such approaches may need to be adapted or deemed inappropriate for the specific context (Nyundo et al, 2021) Table 3.…”
Section: Social Marketing Contextmentioning
confidence: 99%